Pharmacokinetic Drug–Drug Interaction Study Between Raltegravir and Atorvastatin 20 mg in Healthy Volunteers. (1st May 2015) - Blonk, Maren; van Beek, Michiel; Colbers, Angela; Schouwenberg, Bas; Burger, David
Abstract : Background: Dyslipidemia is highly prevalent among patients with HIV infection and contributes to an increased risk of cardiovascular disease. We investigated the influence of a frequently used statin, atorvastatin, on the pharmacokinetics of the HIV-integrase inhibitor raltegravir and vice versa. Methods: Open-label, crossover 3-period phase I trial in 24 healthy volunteers. Subjects took raltegravir 400 mg two times a day for 7 days, atorvastatin 20 mg once a day for 7 days, and the combination of atorvastatin 20 mg once a day + raltegravir 400 mg two times a day for 7 days with 2-week washout periods in between. Intensive steady-state 12- and 24-hour pharmacokinetic blood sampling was performed. Geometric mean ratios of the test treatment (combination raltegravir + atorvastatin) versus the reference treatment (raltegravir or atorvastatin alone) and 90% confidence intervals were calculated for the area under the plasma concentration–time curve (AUC). Fasting lipid profiles were obtained to assess short-term lipid-lowering effect of atorvastatin with or without concomitant raltegravir use. Results: Twenty-four healthy volunteers (11 males) were enrolled. All but 1 subject completed the trial, and no serious adverse events were reported. Geometric mean ratios (90% confidence interval) were 1.01 (0.68–1.51) for raltegravir AUC0–12h and 1.00 (0.90–1.11) for atorvastatin AUC0–24h. The AUC0–24h metabolite-to-parent ratio for atorvastatin lactone, ortho-hydroxy, and para-hydroxy atorvastatin did not change during concomitant raltegravir use. The effect of atorvastatin on low-density lipoprotein cholesterol was not significantly different when combined with raltegravir versus atorvastatin alone ( P = 0.638). Conclusions: Atorvastatin 20 mg has no clinically relevant effect on the pharmacokinetics of raltegravir and vice versa. The combination was well tolerated and can be administered without dose adjustments. Abstract : Supplemental Digital Content is Available in the Text.